A high-concentrate diet induces inflammatory injury via regulating Ca2+/CaMKKβ-mediated autophagy in mammary gland tissue of dairy cows - Meng, Meijuan; Li, Xuerui; Wang, Zihan; Huo, Ran; Ma, Nana; Chang, Guangjun; Shen, Xiangzhen (Frontiers in Immunology, 2023)
Calmodulin-dependent protein kinase β (CaMKKβ) is closely related to Ca2+ concentration. An increase in Ca2+ concentration in the cytoplasm activates CaMKKβ, and activated CaMKKβ affects the activities of AMPK and mTOR and induces autophagy. A high-concentrate diet leads to Ca2+ disorder in mammary gland tissue. Therefore, this study mainly investigated the induction of mammary gland tissue autophagy by a high-concentrate diet and the specific mechanism of lipopolysaccharide (LPS)-induced autophagy in bovine mammary epithelial cells (BMECs). Twelve mid-lactation Holstein dairy cows were fed with a 40% concentrate diet (LC) and a 60% concentrate diet (HC) for 3 weeks. At the end of the trial, rumen fluid, lacteal vein blood, and mammary gland tissue were collected. The results showed that the HC diet significantly decreased rumen fluid pH, with a pH lower than 5.6 for more than 3 h, indicating successfully induction of subacute rumen acidosis (SARA). The HC diet increased the concentration of Ca2+ in mammary gland tissue and pro-inflammatory factors in plasma. The HC diet also significantly increased the expression of CaMKKβ, AMPK, and autophagy-related proteins, resulting in mammary gland tissue injury. The mechanism of LPS-induced autophagy in BMECs was studied in vitro. First, the cells were divided into a Ctrl group and LPS group to study the effects of LPS on the concentration of Ca2+ and autophagy in BMECs. Then, cells were pretreated with an AMPK inhibitor (compound C) or CaMKKβ inhibitor (STO-609) to investigate whether the CaMKKβ–AMPK signaling pathway is involved in LPS-induced BMEC autophagy. LPS increased intracellular Ca2+ concentration and upregulated protein expression of CaMKKβ, AMPK, and autophagy-related proteins. Compound C pretreatment decreased the expression of proteins related to autophagy and inflammation. In addition, STO-609 pretreatment not only reversed LPS-induced BMECs autophagy but also inhibited the protein expression of AMPK, thereby alleviating the inflammatory response in BMECs. These results suggest that inhibition of the Ca2+/CaMKKβ–AMPK signaling pathway reduces LPS-induced autophagy, thereby alleviating inflammatory injury of BMECs. Therefore, SARA may increase the expression of CaMKKβ by increasing Ca2+ levels and activate autophagy through the AMPK signaling pathway, thereby inducing inflammatory injury in mammary gland tissue of dairy cows.